The good parenting food guide : managing what children eat without making food a problem - Ogden, Jane, 1966- (Malden, MA : Wiley Blackwell, 2014)
"The Good Parenting Food Guide offers straightforward advice for how to encourage children to develop a healthy, unproblematic approach to eating. Explores key aspects of children's eating behavior, including how children learn to like food, the role of food in their life and how habits are formed and can be changed Discusses common problems with children's diets, including picky eating, under-eating, overeating, obesity, eating disorders and how to deal with a child who is critical of how they look Turns current research and data into practical tips Filled with practical solutions, take home points, drawings, and photos "--
"The book describes current theory and research and turns this into practical tips for use in every day family life"--
Introduction -- Facts and theories -- 1. What is healthy eating? -- 2. How do we learn to like the food we like? -- 3. What does food mean to us and what role does it play in our lives? -- 4. Why are eating habits so hard to change? -- 5. Overweight and obesity: prevalence, consequences, and causes -- 6. Overweight and obesity: prevention and treatments -- 7. Eating disorders: prevalence, consequences, and causes -- 8. Eating disorders: prevention and treatments -- Tips and reality -- 9. "I don't have time to cook" -- 10. "My child won't eat a healthy diet" -- 11. "My child watches too much TV": tips for being more active -- 12. "My child eats too much" -- 13. "My child won't eat enough" -- 14. "My child thinks they are fat" -- 15. Take home points.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Children -- Nutrition -- Popular works; Eating disorders in children -- Popular works; Obesity in children -- Popular works; PSYCHOLOGY -- Physiological Psychology; Children -- Nutrition; Eating disorders in children; Obesity in children; Electronic books; Popular works